Comparing oral health-related quality of life and satisfaction: root canal therapy vs. extraction for first permanent molars in children – a case–control study - Heba Jafar Sabbagh; Ahmad Adnan Samara; Wala Dhafar; Jihan Turkistani; Manal Ibrahim Almalik; Rzan Zaatari; Ahlam Bahkali; Nada Bamashmous (BMC Oral Health)
Abstract Background This study addresses a literature gap by examining Oral Health Related Quality of Life (OHRQoL) and children-parental satisfaction concerning the management of compromised first permanent molars (FPMs) through root canal therapy (RCT) versus extraction. Methods Children who extracted or received RCT and their parents were interviewed using a validated questionnaire that includes sociodemographic data, OHIP5-Ar questionnaire and satisfaction question. Results There were 305 patients with RCT (197 (37.1%)) or extraction (108 (87.8%)). RCT increased the adjusted odds ratio (AOR) of the child’s OHRQoL (3.76; P < 0.001) and parent-satisfaction at assessment-time (AOR = 1.82; P = 0.02). Additionally, increase in the duration between treatment and assessment-time elevated the AOR of patient’s OHRQoL (AOR = 1.69; P = 0.001). Significantly fewer children reported being uncomfortable with the appearance of their teeth following RCT compared to those who underwent extraction (P < 0.001). Although not statistically significant, patients tended to express greater satisfaction with extraction compared to RCT at the assessment-time (AOR: 0.64; P = 0.081). Conclusion While the choice between performing RCT or extraction of compromised FPM in children depends on various factors, both can lead to substantial success in improving the child's OHRQoL and satisfaction. Nevertheless, RCT resulted in fewer concerns about dental appearance.